Analysis of radiation exposure data from common radiological procedures in Dutch hospitals. Issue 3 (August 2020) - Bijwaard, H.; de Vries, G.; de Waard-Schalkx, I.; van Welie, F.; Haarmans-Jonkman, S.; Erenstein, H.; Scheurleer, J.; Roding, T.; Middendorp, I.V.; van der Ploeg, T.
Abstract: Introduction: In the Netherlands, Diagnostic Reference Levels (DRLs) have not been based on a national survey as proposed by ICRP. Instead, local exposure data, expert judgment and the international scientific literature were used as sources. This study investigated whether the current DRLs are reasonable for Dutch radiological practice. Methods: A national project was set up, in which radiography students carried out dose measurements in hospitals supervised by medical physicists. The project ran from 2014 to 2017 and dose values were analysed for a trend over time. In the absence of such a trend, the joint yearly data sets were considered a single data set and were analysed together. In this way the national project mimicked a national survey. Results: For six out of eleven radiological procedures enough data was collected for further analysis. In the first step of the analysis no trend was found over time for any of these procedures. In the second step the joint analysis lead to suggestions for five new DRL values that are far below the current ones. The new DRLs are based on the 75 percentile values of the distributions of all dose data per procedure. Conclusion: The results show that the current DRLs are too high for five of the six procedures that have been analysed. For the other five procedures more data needs to be collected. Moreover, the mean weights of the patients are higher than expected. This introduces bias when these are not recorded and the mean weight is assumed to be 77 kg. Implications for practice: The current checking of doses for compliance with the DRLs needs to be changed. Both the procedure (regarding weights) and the values of the DRLs should be updated.